Evaluation of supply chain performance : a manufacturing industry approach /: a manufacturing industry approach. ([2019]) - Avelar-Sosa, Liliana; García-Alcaraz, Jorge Luis; Maldonado-Macías, Aidé Aracely
No abstract available